2005
DOI: 10.1097/01.mao.0000185075.58199.22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bilaterally Implanted Adult Subjects with the Nucleus 24 Cochlear Implant System

Abstract: There is a significant bilateral advantage of adding a second ear for this group. We were unable to predict when the second ear would be the better performing ear, and by implanting both ears, we guarantee implanting the better ear. Sequential implantation with long delays between ears has resulted in poor second ear performance for some subjects and has limited the degree of bilateral benefit that can be obtained by these users. The dual microphone does not provide equivalent benefit to bilateral implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 10 publications
6
100
4
1
Order By: Relevance
“…In particular, bilateral stimulation can provide a substantial benefit in recognizing difficult speech materials such as monosyllabic words and in recognizing speech presented in competition with spatially distinct noise, in comparison to scores obtained with either unilateral implant alone (e.g., Gantz et al, 2002;Müller et al, 2002;Laszig et al, 2004;Ramsden et al, 2005;Litovsky et al, 2006;Ricketts et al, 2006). In addition, use of both implants supports an improved ability to lateralize or localize sounds (depending on which was measured in a particular study), again compared with either unilateral implant (e.g., van Hoesel and Tyler, 2003;Nopp et al, 2004;Senn et al, 2005;Grantham et al, 2007;Tyler et al, 2007).…”
Section: Two Recent Advancesmentioning
confidence: 99%
“…In particular, bilateral stimulation can provide a substantial benefit in recognizing difficult speech materials such as monosyllabic words and in recognizing speech presented in competition with spatially distinct noise, in comparison to scores obtained with either unilateral implant alone (e.g., Gantz et al, 2002;Müller et al, 2002;Laszig et al, 2004;Ramsden et al, 2005;Litovsky et al, 2006;Ricketts et al, 2006). In addition, use of both implants supports an improved ability to lateralize or localize sounds (depending on which was measured in a particular study), again compared with either unilateral implant (e.g., van Hoesel and Tyler, 2003;Nopp et al, 2004;Senn et al, 2005;Grantham et al, 2007;Tyler et al, 2007).…”
Section: Two Recent Advancesmentioning
confidence: 99%
“…Sequential implantation in 28 adults with 1 to 7 years between ears resulted in poor performance in the second implanted ear for subjects who had longer periods of time between implanted sides [74]. After 9 months of stimulation in the second ear, scores were poorer in noise in the second ear than the first ear.…”
Section: Speech Recognition: Sequential Implantationmentioning
confidence: 99%
“…For CI recipients using a dual microphone at each ear coupled to a single CI system, speech-recognition performance has been shown to be poorer than with bilateral implants [74,94,100]. Bilateral microphones with a single implant, therefore, do not achieve the binaural processing capabilities that may be afforded by bilateral implants.…”
Section: Fitting Of Bilateral Implantsmentioning
confidence: 99%
“…These results are consistent with those seen in other studies such as Gibson and Sanli (2007) who showed 32/39 children with good EABR results and good functional outcomes. It is possible that the poorer functional outcomes measured in the subsequently implanted ear arose from the prolonged delay in implanting the second ear (Ramsden et al, 2005;Gordon et al, 2008) although conflicting evidence exists about the impact of duration of sequential implantation on functional outcomes (Zeitler et al, 2008). In any case, in contrast to Case 1, Case 2 provides an example of a subset of individuals identified as having ANSD with additional confounding factors, including cerebral palsy, developmental delay, Autism Spectrum Disorder.…”
Section: Role Of Evoked Potentials In Decision-makingmentioning
confidence: 98%